Analisis Kualitas Layanan Aplikasi Prestige Di Kabupaten Gresik Menggunakan Metode ServQual - Yuhansyah, Riski Ilham; Putri, Devita Maulina (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The Prestige application is an online attendance for Gresik Regency ASN. What is the assessment of the feasibility of the functionality of the Prestige Application, and what factors influence employees dissatisfaction with the Prestige Application. In previous research on attendance applications, only regarding the impact of the application on employee performance. This research tests the application functionality, so that it meets what is required. Researchers as instruments and data collectors provide assessments of the Prestige application, finding problems that result in a decrease in the quality of the Prestige application. The ServQual method or what is called the service quality concept is a method used to test the nature of service quality, and involves 90 questionnaire respondents. In this research, it was found that there is no forget password feature, and importantly there is a feature to display the total number of attendance points. The Reliability dimension gets the largest value, and the Empathy dimension gets the smallest value. As input, BKPSDM needs to add a forget password feature and information regarding total employee attendance points.